The Annotated Laozi: A New Translation of the Daodejing - Fischer, Paul; Laozi 4 v. Chr. (SUNY Series in Chinese Philosophy and Culture Series, 2023)
A clear translation and helpful explanations illuminate this ancient classic of self-cultivation for a modern audience.